The italian matchmaker eaudiobook - Montefiore, Santa (Recorded Books Inc., 2010)
In a lush tale shortlisted for the Romantic Novel of the Year Award, Santa Montefiore spotlights a man whose high-flying career and glitzy paramours no longer satisfy. With his marriage dead and his daughters strangers, Gianluca retreats to an Italian villa to seek peace and purpose. But when he finds the sun-drenched Palazzo Montelimone overrun with eccentric people and haunted by ghosts from its bloody past, he must confront his greatest fear to unravel a dark secret.